STUDI PEMIKIRAN SITI MUSDAH MULIA TERHADAP TINDAK PEMUKULAN KEKERASAN RUMAH TANGGA SEBAGAI ALASAN TAHAPAN PERCERAIAN DALAM HUKUM ISLAM - Uswatun Hasanah; Donny Meilano (Usroh: Jurnal Hukum Keluarga Islam, 2021)
Problems arise between husband and wife who cannot fulfill their role in domestic relations, both behavior and attitudes to control themselves are difficult to implement, instead, divorce and occur when inequality, disharmony and strife between husband and wife can lead to acts of violence. This study uses a library research type of research method, obtained from secondary data sources. To obtain secondary legal sources, the legal source approach is used, namely primary, secondary and tertiary data. The data that has been obtained is processed and analyzed using deductive, inductive and qualitative descriptive methods. The results of the analysis of this study in the Qur'an to overcome the actions of the wife who are nusyuz through the first three stages the husband must first advise the wife so that the wife is aware that her actions have violated the rules in the household, if this does not make the wife aware then the husband is recommended to do the second stage by separate beds so that the wife is aware that her actions have violated the rules, but if it does not work then it is permissible to hit with a note that it does not hurt, hitting with a part that does not harm his wife such as the calf. Meanwhile, Siti Musdah Mulia is of the opinion that she does not recommend beatings because it is feared that beatings can result in domestic violence if it occurs continuously and can reach the stage of divorce.